A study on coke deposition in Ni-based catalysts for CO2 reforming of methane - Yahya, E.A. (American Institute of Physics Inc., 2016)
Cobalt (Co) and niobium (Nb) promoted Ni-based catalysts have been prepared by a wet impregnation method. The influence of these promoters on properties and performance of Ni-based catalyst supported on Î³-Al2O3 for CO2 reforming of methane reaction has been studied. CO2 reforming of methane reaction has been conducted at atmospheric pressure for 5 h at 850Â°C. Results show that Nb promoted catalysts show higher conversion of CH4 and CO2 (44.5) compared to that of unpromoted catalyst. Meanwhile, the amount of coke formed was lower on the promoted catalysts compared to that of unpromoted catalyst. Â© 2016 Author(s).